Expression of Three Cell Adhesion Molecules in Bladder Carcinomas: Correlation with Pathological Features - Agnès Mialhe; Josette Louis; Dominique Pasquier; Jean‐Jacques Rambeaud; Daniel Seigneurin (Analytical Cellular Pathology)
Recently, independent studies have shown that the expression of two integrin chains, β4 and α2, plus the epithelial cadherin are related to tumour progression in human bladder carcinomas. For the first time, we compare the expression of these three cell adhesion molecules using immunohistochemical analysis of consecutive cryosections from a series of 50 bladder tumours. E‐cadherin, β4, and α2 were strongly expressed in normal urothelium. A majority of non‐invasive bladder cancers stained positively for E‐cadherin (62%), whereas only 29% expressed normal positivity for α2, and only 35% for β4. However, most invasive tumours presented an aberrant expression of α2 (81%), β4 (100%), and E‐cadherin (75%). We studied the correlation of immunoreactivity with histological grade and stage. The α2 pattern was not correlated with stage and grade. In contrast, loss of normal β4 expression was significantly related to increasing tumour grade and deep invasion with a higher correlation for grade. Finally, E‐cadherin expression was highly correlated with stage, but not with grade. Thus our results indicate that, although many invasive bladder tumours presented a disorder in expression of the two integrins α2 and β4, E‐cadherin appeared to be a better marker of invasiveness in bladder carcinomas.